Od napięcia do zbrojnego konfliktu: stosunki litewsko-polskie na Wileńszczyźnie w lataсh 1939–1945 - Stravinskienė, Vitalija (Східноєвропейський національний університет імені Лесі Українки, 2019)
In the course of history the relations between Lithuania and Poland went through several stages: from concord to hostility and an armed conflict during World War II, their “freeze” during the years of Soviet power (1944–1989) and normalisation after the country’s independence has been restored. The period of World War II, especially the years of the German occupation, is attributed to the complicated stages of Lithuanian and Polish relations (1941–1944). After occupying Lithuania the Nazi authorities exploited the country and its inhabitants, sought to fulfil its military-political and economic aims and incited interethnic hatred and antagonism between the Lithuanians and Poles in Vilnius region. Hatred and antagonism manifested themselves in the most various forms: beginning with everyday conflicts (for example, at food stores) and finishing with armed conflicts (the most brutal case was massacre of the civil Polish and Lithuanian citizens in Glitiškės and Dubingiai). The main cause of the conflict between the Lithuanians and Poles, as during the interwar period, was the issue of the state dependence of Vilnius. During the years of the Nazi occupation neither Lithuanians nor Poles were real owners of Vilnius and its region, a disguised, and sometimes open, struggle for influence in Vilnius region was going on. Having occupied Lithuania, the Nazis organised different campaigns (recruitment of people for work in Germany, preparation to settle German colonists in Lithuania, etc.) with the hands of the Lithuanians thus provoking and directing antagonism of the Polish people against the Lithuanians. However, the Nazi “support” came to an end in 1943 when the Lithuanians resisted the establishment of the SS legion. A different attitude to their friends (the Soviet Union was enemy No. 1 to the Lithuanian and the Poles considered Nazi Germany its enemy No. 1), fighting tactics, the use of Lithuanian self-defence units and security police for punitive campaigns against the inhabitants of Vilnius region (the Poles constituted the larger part thereof), the anti-Lithuanian activities of some Polish underground guerrilla groups also complicated the relations between the Lithuanians and Poles (Armia Krajowa [Home Army]). The last stage of the interethnic tension between the Lithuanians and Poles started in July 1944 when the soviet army entered the territory of Lithuania. The Soviet Union, which reoccupied Lithuania, resolved the Lithuanian-Polish conflict by means of the method of displacement of the inhabitants. Between 1944 and 1946, the majority of the Polish inhabitants from Vilnius and Vilnius region were compelled to move to Poland that appeared in a new geographical space. In this way the former Lithuanian-Polish conflict was suppressed and “frozen” for several decades.